2021
DOI: 10.1101/2021.12.01.470875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial community response to species overrepresentation or omission is strongly influenced by life in spatially structured habitats

Abstract: Variations in type and strength of interspecific interactions in natural bacterial communities (e.g., synergistic to inhibitory) affect species composition and community functioning. The extent of interspecific interactions is often modulated by environmental factors that constrain diffusion pathways and cell mobility and limit community spatial arrangement. We studied how spatially structured habitats affect interspecific interactions and influence the resulting bacterial community composition. We used a bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Less common methods to measure composition include: dilution plating on different selective medias and counting CFUs (colony forming units) ( Wu et al, 2022 ), which is laborious and slow; qPCR (quantitative Polymerase Chain Reaction) of unique DNA sequences ( Mee et al, 2014 ; Jian et al, 2020 ; Kleyer, Tecon and Or, 2021 ); or RNA sensors on paper-based cell-free systems ( Takahashi et al, 2018 ). qPCR and RNA sensors can be quantitative and cost effective, but typically require primer/RNA sensor design for each species and involve laborious sample extraction and amplification.…”
Section: Control Output: Measuring Community Compositionmentioning
confidence: 99%
“…Less common methods to measure composition include: dilution plating on different selective medias and counting CFUs (colony forming units) ( Wu et al, 2022 ), which is laborious and slow; qPCR (quantitative Polymerase Chain Reaction) of unique DNA sequences ( Mee et al, 2014 ; Jian et al, 2020 ; Kleyer, Tecon and Or, 2021 ); or RNA sensors on paper-based cell-free systems ( Takahashi et al, 2018 ). qPCR and RNA sensors can be quantitative and cost effective, but typically require primer/RNA sensor design for each species and involve laborious sample extraction and amplification.…”
Section: Control Output: Measuring Community Compositionmentioning
confidence: 99%
“…Within these communities, bacterial pathogens compete with their neighbors for space and resources (Hibbing et al., 2010). Recent reports also demonstrated that life in such structured habitats alters the composition of microbial communities compared to liquid cultures (Kleyer et al., 2021). The recent development of high‐throughput DNA sequencing technologies allows a new approach that is free from the limitations of culture‐dependent experiments and which describes microbial communities in food matrices with unprecedented resolution (Ercolini, 2013).…”
Section: Physiological Heterogeneity: Bacterial Cell Response To Food...mentioning
confidence: 99%